PATIENTS’ PSYCHOSOMATIC STATUS BEFORE AND AFTER ORTHOPEDIC CORRECTION OF MAXILLOFACIAL DEFECTS - A. A. Kulakov; V. M. Chuchkov; E. G. Matyakin; I. S. Romanov; A. A. Akhundov; A. M. Mudunov; S. P. Fedotenko; N. N. Fedotov; S. O. Podvyaznikov; M. A. Kropotov; T. Yu. Marilova; M. M. Tarasova; et al. (Опухоли головы и шеи)
A medicopsychological study of the time course of psychic changes was conducted in 88 cancer patients with defects of facial soft tissues (n = 38) and maxilla (n = 50). Since the patients’ visit to an oncologist, the diagnostic-stage depth of mental disorders was rather various: from mild asthenia to depression. Thus, 88 (100 %) patients were found to have an anxious feeling, 16 (18.2 %) had affective-shock reactions; 7 (7.9 %) had reactive depression. In the postoperative period, anxiety-depressive syndrome gave way to astheno-depressive one. After hospital discharge, the reactive state became less tense during psychosocial readaptation, the characteriological personality changes were increasingly more pronounced in the forefront in the patients. They became anxious, suspicious, unconfident about themselves, sensitive, tried to avoid difficult situations in life. The circle of interests was limited to thoughts on their own health. Combination therapy with psychotropic drugs was used to correct the mental status of patients with acquired maxillary defects in the study group. The dosage of the drugs was individually adjusted according to the degree of psychopathological manifestations.